Efektivitas Aromaterapi Pappermint Oil terhadap Peningkatan Kualitas Tidur pada Pasien Stroke di Wilayah Kerja Puskesmas Barebbo, Kabupaten Bone - A. Artifasari; Mardiana Mardiana; Irawati Irawati (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
Stroke is a neurological disorder caused by impaired blood flow to the brain, resulting in brain tissue damage and various functional impairments. One of the common problems experienced by stroke patients is sleep disturbance, which may be influenced by neurological deficits, limited physical mobility, pain, and post-stroke anxiety. Persistent sleep disturbances can delay the recovery process and reduce patients’ quality of life. The long-term use of sleeping medications may lead to adverse effects; therefore, safe and easily applicable complementary therapies are needed. This study aimed to determine the effectiveness of peppermint oil aromatherapy in improving sleep quality among stroke patients in the working area of Barebbo Community Health Center, Bone Regency. The method used was the implementation of complementary therapy through the administration of peppermint oil aromatherapy to stroke patients experiencing sleep disturbances. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. The assessment results showed that before the intervention, patients experienced poor sleep quality, characterized by difficulty initiating sleep, frequent nighttime awakenings, insufficient sleep duration, and daytime fatigue. After receiving peppermint oil aromatherapy, patients demonstrated increased comfort, reduced anxiety, improved ability to initiate sleep, and better overall sleep quality compared to their condition before the intervention. Therefore, peppermint oil aromatherapy was found to be effective in improving sleep quality among stroke patients and can be used as a complementary non-pharmacological intervention in nursing care.